2021
DOI: 10.1038/s41598-021-89785-1
|View full text |Cite
|
Sign up to set email alerts
|

A PROSS-designed extensively mutated estrogen receptor α variant displays enhanced thermal stability while retaining native allosteric regulation and structure

Abstract: Protein stability limitations often hamper the exploration of proteins as drug targets. Here, we show that the application of PROSS server algorithms to the ligand-binding domain of human estrogen receptor alpha (hERα) enabled the development of variant ERPRS* that comprises 24 amino acid substitutions and exhibits multiple improved characteristics. The protein displays enhanced production rates in E. coli, crystallizes readily and its thermal stability is increased significantly by 23 °C. hERα is a nuclear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…9 C ). However, this salt bridge is neither conserved across herpesviruses nor appears to be subfamily-specific although surface-located salt bridges have been shown to increase the structural stability of proteins ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 C ). However, this salt bridge is neither conserved across herpesviruses nor appears to be subfamily-specific although surface-located salt bridges have been shown to increase the structural stability of proteins ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also showed similar improvements in thermostabilization of the activated ER. 50,51 Although the holo ER wt has similar T m values at both pHs, apo ER wt presents different values at pH 6.0 (T m = 43) and pH 8.0 (T m = 48). Such a result may be attributed to the stronger tendency of H12 to reach its closed state at the higher pH, even in the absence of E2.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…This combination of sequence-based and structure-based design has been successfully implemented in two computational tools, PROSS and FireProt, that aim to redesign proteins for increased thermostability and expression. ,,, PROSS uses the observed amino acid frequencies at each position in a multiple-sequence alignment to define a set of “allowed” substitutions in the target protein on the basis of their occurrence in homologous proteins (Figure ). Allowed substitutions that have a stabilizing effect on protein structure are predicted using structure-based energy calculations, and mutually compatible combinations of these substitutions are then predicted by combinatorial protein design in Rosetta, yielding a small number of designed sequences for experimental testing with substitutions at ≲10% of positions.…”
Section: Structure-based Design Guided By Sequence Informationmentioning
confidence: 99%